Ryugu’s observed volatile loss did not arise from impact heating alone - Kosuke Kurosawa (Nature Portfolio, 2021)
The loss of volatile material from asteroid Ryugu was not caused solely by heating from hypervelocity impacts as previously believed, suggest impact experiments conducted at speeds comparable to those expected in the main asteroid belt